The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mbo3.645
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term direct contact with soil and plant materials leads to an immediate increase in diversity of skin microbiota

Abstract: Immune-mediated diseases have increased during the last decades in urban environments. The hygiene hypothesis suggests that increased hygiene level and reduced contacts with natural biodiversity are related to the increase in immune-mediated diseases. We tested whether short-time contact with microbiologically diverse nature-based materials immediately change bacterial diversity on human skin. We tested direct skin contact, as two volunteers rubbed their hands with sixteen soil and plant based materials, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 69 publications
(99 reference statements)
4
51
0
Order By: Relevance
“…The samples were anonymised and used in the development of antibody tests. Control serum samples included laboratory personnel and the participants of the Autoimmune defence and living environment-study (ADELE) [18] and negative control samples from 6-month old children who were participating in the Diabetes prediction and prevention-study (DIPP) [19]. All participants or their legal guardians gave informed consent.…”
Section: Human Samples Ethics Statementmentioning
confidence: 99%
“…The samples were anonymised and used in the development of antibody tests. Control serum samples included laboratory personnel and the participants of the Autoimmune defence and living environment-study (ADELE) [18] and negative control samples from 6-month old children who were participating in the Diabetes prediction and prevention-study (DIPP) [19]. All participants or their legal guardians gave informed consent.…”
Section: Human Samples Ethics Statementmentioning
confidence: 99%
“…The emerging research on soil-based interventions (e.g., handling a mossy soil-plant composition) demonstrates that ecological considerations are not confined to capsules. Indeed, daily contact with external microbiomes may influence internal ecosystems [118,119]. This suggests another pathway (beyond what is described as social and psychological) by which personal, school, and community gardening provide their health benefits [120,121].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Here, we empirically characterized fine-scale dynamics after a whole-community microbial transmission event to human skin, describing the relationship between initial abundance in the donor community and persistence through time. While it has been demonstrated that such contact events lead to an increase in skin microbial diversity (57) , and that the microbiome of the skin is both highly diverse and highly variable across longer time scales (6) , the fine-scale dynamics of microbial transmission through such contact events has not been previously characterized.…”
Section: Discussionmentioning
confidence: 99%